Architecture of the Rangamandapa of the Ghateshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Ghateshwar Temple has a rangamandapa (open type of pillared hall used for ceremonial rituals) on the eastern end of the east-west axis, which is larger than the mukhamandapa (front porch). The rangamandapa also known as Shringara Chaori has low base mouldings on which large number of pillars stands, supporting the phamsana shikhara (pyramidal superstructure).